A tertiary centre experience of vulval crohn's disease. (13th March 2011) - Landy, J; Peake, S T; Akbar, A; Hart, A L
Abstract : Introduction: Crohn's disease affecting the vulva is rarely described and often difficult to treat. The authors describe their experience of 20 patients with vulval Crohn's disease, which to their knowledge is the largest series described in the literature to date. Methods: The IBD database from 2006 to 2010 was searched for the terms 'vulva', 'vulval' and 'Crohn's'. The case notes identified by this search were reviewed. Results: Demographics. The median age of Crohn's disease diagnosis was 19 years (range 11–40 years). Vulval disease was the primary presentation of Crohn's disease in 2 patients. All the patients were premenopausal. The median age of vulval involvement was 27.5 years (range 19–50 years) and the median interval from Crohn's disease diagnosis to vulval disease was 9 years (range 0–32 years). 7 patients were smokers and 2 had a family history of inflammatory bowel disease. Distribution. 3 patients had metastatic disease (arising independently from other areas of Crohn's disease) while 17 had vulval involvement contiguous with perianal disease. Of the 3 patients with metastatic disease, 2 had colonic involvement and 1 ileocolonic disease distribution. Disease Severity . 11 patients had previously undergone at least 1 surgery for their Crohn's diseases. 1 patient had concomitant upper GI involvement and 3 had stricturing or penetrating disease. 4 patients had other extraintestinal manifestations (all arthropathy). Diagnosis. 5 patients were biopsied to confirm the diagnosis of vulval Crohn's. Presenting symptoms included vulval swelling (n=9), discharge (n=7), pruritus (n=1), pain (n=6), erythema (n=8), vulval ulceration (n=2) and vulval abscess (n=7). Treatment. 10 patients received antibiotics, 2 topical steroids, 12 thiopurines, 3 methotrexate, 3 topical tacrolimus and 9 biologic therapy. Of those receiving an anti-TNF treatment, 8 received Infliximab first and 1 adalimumab. 1 patient had an infusion reaction, 3 had no response. Of the 5 primary responders, 3 lost response. 1 regained response with increased frequency of Infliximab, 2 patients were switched to adalimumab. Conclusion: In this group with vulval Crohn's disease, patients predominantly had contiguous disease from perianal or rectal concurrent disease. Metastatic disease was uncommon. The majority of patients with vulval Crohn's had a severe course of their disease. Presentation was varied. There was a limited response with topical tacrolimus and 5 patients responded to anti-TNF therapy. Vulval Crohn's disease is associated with severe disease and should be suspected with patients with Crohn's disease and vulval symptoms. In keeping with previous case reports, anti-TNF therapy may be of benefit for some patients with vulval Crohn's disease.